2019
DOI: 10.29252/jafm.12.06.29938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Bogie Cavity Configurations on the Underbody Flow and Near Wake Structures of a High-Speed Train

Abstract: A time-dependent simulation method, DES (detached eddy simulation), combined with Realizable k-ε turbulence model, has been adopted to study the underbody flow and near wake structures of a high-speed train with two bogie cavity configurations laid on the stationary ground. The numerical data, including timeaveraged aerodynamic drag forces and pressure coefficients, were compared with experimental results from previous wind tunnel tests. A detail comparison of the instantaneous flow structures, mean velocity v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The boundary layer was generated on the surface of the car body. The first layer height of the boundary grid was 0.3 mm, such that the y+ meets the requirement (50<y+<180, Deng et al 2019;Xu et al 2019) and the calculation parameters are shown in Table 1, where the growth ratio is 1.2, the total number of layers is 4, and the number of grids is about 12.5 million. The computational grids are shown in Fig.…”
Section: Computational Meshing and Numerical Methodsmentioning
confidence: 99%
“…The boundary layer was generated on the surface of the car body. The first layer height of the boundary grid was 0.3 mm, such that the y+ meets the requirement (50<y+<180, Deng et al 2019;Xu et al 2019) and the calculation parameters are shown in Table 1, where the growth ratio is 1.2, the total number of layers is 4, and the number of grids is about 12.5 million. The computational grids are shown in Fig.…”
Section: Computational Meshing and Numerical Methodsmentioning
confidence: 99%
“…A sliding wall is set on the track wall to simulate the relative motion between the train and the track. The turbulence model selects the RNG k − two-equation turbulence model [22,23]. The calculation method adopts the SIMPLE [Semi-Implicit Method for Pressure Linked Equations] algorithm and uses the second-order upwind style to discretize the computational domain to solve the three-dimensional, steady, incompressible turbulent flow around the high-speed train.…”
Section: Computational Grid and Numerical Methodsmentioning
confidence: 99%